Investigation of triple and evaluation of re-ranking technique in HTML document / Ninie Sumarni Abdullah - Abdullah, Ninie Sumarni (2014)
Search engine is used to retrieve information from the World Wide Web. However there is a deluge amount of documents retrieved by a given query from the user. Users are having a difficulty in selecting and acquiring the valuable information. With existence of semantic search engine, users can simply.acquire relevant document that is sufficient enough that answer user query. Research has been shown that semantic search engine performs better than available search engine. However to build a semantic search engine requires representing deluge information in triples. In this project. Triple from html documents are studied. Next, matched html documents are rank according to re-ranking technique. Result show that there is an improvement of the listed html documents in term of relevancy.